2009
DOI: 10.5536/kjps.2009.36.1.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corn Distiller's Dried Grains with Solubles on Production Performance and Economics in Laying Hens

Abstract: A 10-wk layer feeding trial was conducted to investigate the effects of high quality corn distiller's dried grains with solubles (DDGS) on performance, egg qualities, and yolk fatty acid composition. The economics of using DDGS in the Korean situation was also analyzed. A total of 216 Hy-line Brown layers, 23-wk of age, were employed in this trial consisting of three dietary treatments (0%, 10%, and 20% DDGS), and six replicates per treatment. All experimental diets were prepared as iso-protein (17%) and iso-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Total saturated and unsaturated fatty acids among four DDGS treatments were not significantly different; however total polyunsaturated fatty acids increased linearly as dietary DDGS level increased. This result agrees with the study of Rew et al (2009) who reported that 20% DDGS diet resulted in increased polyunsaturated fatty acids in egg yolk. Schilling et al…”
Section: Resultssupporting
confidence: 93%
“…Total saturated and unsaturated fatty acids among four DDGS treatments were not significantly different; however total polyunsaturated fatty acids increased linearly as dietary DDGS level increased. This result agrees with the study of Rew et al (2009) who reported that 20% DDGS diet resulted in increased polyunsaturated fatty acids in egg yolk. Schilling et al…”
Section: Resultssupporting
confidence: 93%
“…In the first trial, Cheon et al (2008) investigated the effects of corn DDGS (0, 10, 15 and 20%) on egg production and quality, and reported that the use of DDGS up to 20% in layer diets did not exert any influence on feed intake, laying rate, total egg mass, mean egg weight and feed efficiency, but the yolk colour and linoleic acid content were significantly increased by DDGS supplementation. More recently, in another trial, Rew et al (2009) researched the effects of corn DDGS (0, 10 and 20%) on production performance and economics in laying hens and observed very similar results as obtained by Cheon et al (2008). More recently, in another trial, Rew et al (2009) researched the effects of corn DDGS (0, 10 and 20%) on production performance and economics in laying hens and observed very similar results as obtained by Cheon et al (2008).…”
Section: Use Of Ddgs For Laying Hensmentioning
confidence: 55%
“…However, the feed cost per kg egg of 15% DDGS supplementation group was very much comparable to that of no DDGS supplementation group. Rew et al (2009) investigated the effects of using corn DDGS (0, 10 and 20%) on production performance and economics in laying hens and observed very similar results Asian J. Anim.…”
Section: Economicsmentioning
confidence: 78%